2019
DOI: 10.1051/matecconf/201930401013
|View full text |Cite
|
Sign up to set email alerts
|

Computation of mechanical, thermal and electrical properties of CNT/polymer multifunctional nanocomposites using numerical and analytical models

Abstract: In the present work, the mechanical, thermal and electrical properties of CNT/polymer nanocomposites are computed using numerical and analytical models as functions of material parameters (CNT aspect ratio, CNT waviness, presence of the interphase) and processing factors (CNT volume fraction, formation of agglomerates and the number and arrangement of CNTs in the agglomerates). The computation is performed using representative unit cells (RUCs) of CNT agglomerates. The RUCs are solved numerically using the FE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Based on the literature data [12][13][14][15] devoted to the study of dispersed-filled composites based on thermoplastic polymers, it can be concluded that their properties are determined by the content and shape of particles. One of the significant factors affecting the mechanical properties of the composite is the orientation of fibers in space.…”
Section: Methods Of Computer Modeling Of the Mechanical Properties Of The Designed Compositementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature data [12][13][14][15] devoted to the study of dispersed-filled composites based on thermoplastic polymers, it can be concluded that their properties are determined by the content and shape of particles. One of the significant factors affecting the mechanical properties of the composite is the orientation of fibers in space.…”
Section: Methods Of Computer Modeling Of the Mechanical Properties Of The Designed Compositementioning
confidence: 99%
“…Various techniques based on analytical and numerical methods of thermophysics and mechanics of composite materials are currently used to model and predict the physical properties of composite materials. In [12], the mechanical, thermal and electrical properties of multifunctional CNT/polymer nanocomposites are calculated using numerical and analytical models depending on the material parameters and processing factors. The influence of the content and size of inclusions was determined in the paper.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…20,21 Tserpes et al performed a study based on finite element analysis and Mori-Tanaka (M-T) model to capture all three properties (elastic, thermal, and electrical) of CNT/polymer multifunctional nanocomposites with respect to different parameters like quantity of CNTs, CNT's aspect ratio, CNT's curvature, and interphase. 22 Naskar et al presented different spatial random microstructures for composites using an finite element model (FEM)-based computational study to investigate the manufacturing as well as environmental uncertainties, which are later extended to nanocomposites. 23,24 Mehvari et al analyzed the electrical performance of copper/ polyurethane composite under pressure both experimentally and computationally.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They showed that minimum percolation value and maximum conductivities mostly depend on the polymer type and dispersion method, instead of type and production of CNTs . Because of its extensive surface area, great electrical conductivity, superior mechanical strength, and good stability, CNTs seem promising as an immobilization substance. , Tserpes et al performed a study based on finite element analysis and Mori-Tanaka (M-T) model to capture all three properties (elastic, thermal, and electrical) of CNT/polymer multifunctional nanocomposites with respect to different parameters like quantity of CNTs, CNT’s aspect ratio, CNT’s curvature, and interphase . Naskar et al presented different spatial random microstructures for composites using an finite element model (FEM)-based computational study to investigate the manufacturing as well as environmental uncertainties, which are later extended to nanocomposites. , Mehvari et al analyzed the electrical performance of copper/polyurethane composite under pressure both experimentally and computationally .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation